Poems on the Uí Dhomnaill (circa 1641) - Mac Cárthaigh, Eoin (Trinity College (Dublin, Ireland). Department of Irish and Celtic Studies, 1995)
The concern of this thesis is to produce an edited, translated and annotated text of a set of fifteen poems composed in the mid-seventeenth century in praise of members of the Ó Domhnaill dynasty of Donegal. The main source used is Duanaire Uí Dhomhnaill (‘The Poem Book of the O'Donnells'), a National Library manuscript which was written in the early eighteenth century. Most of the poems conform both metrically and linguistically to the standards of Classical Irish, a literary dialect which emerged in the twelfth century. The strict rules of this language make it possible, for the most part, to restore the poems to the form in which they were composed before corrupt manuscript transmission took its toll on them. The edited text of the poems is accompanied in each instance by a parallel reproduction, in Roman orthography, of the version of the composition found in the main manuscript consulted and by a translation. Where more than one manuscript has been consulted, readings from these other sources are also given. A line-by-line commentary explains any emendations made in the edited text, glosses the translations, identifies significant persons and places referred to in the poems, gives examples (where available) from other sources of idiomatic expressions employed by the poets and draws attention to unusual usages - morphological, semantic, grammatical or syntactic - appearing in the text. An introductory section deals with (i) references, in other primary sources, to the subjects of these poems and other significant members of the Ó Domhnaill dynasty in the period following the Ulster plantation; (ii) identification of the poets; (iii) manuscripts consulted; (iv) the choice of poems, the ordering of poems in the text and previous editions made of four of the poems; (v) the approach taken to editing; (vi) initial mutation; (vii) the use of declensional cases; (viii) other issues of language and metre. Persons and places mentioned in the text are fully indexed; a glossarial index to the textual commentary is also included.
Keywords: Celtic Language and Literature, Ph.D.; Ph.D. thesis Trinity College Dublin, 1995